The impact of dividend policy on share price volatility in the Macedonian stock market - Aleksandra Mladenoska (Journal of Contemporary Economic and Business Issues, 2017)
The intention of this paper is to examine the relationship between the dividend policy and share prices of companies on the Macedonian Stock Exchange in order to define whether the dividend policy is a factor determining the share price volatility, and if so, how to use this possibility to influence the company's value. For that purpose, 110 profit distribution decisions were analyzed (10 companies, 11 years, 2006 - 2016). The relationship between the dividend policy and share prices was examined by dummy variables in Regression analysis and Panel regression analysis. A Dummy variable regression model is used when determining the movement of share prices around dividend payment dates, whilst a Panel data regression model is used when determining the effect of change in dividends on share price change. Empirical results have shown that: First, in the quarter when the decision on dividend payment is declared, the share price goes up by 9%. Second, on the ex-dividend date, the share price decreases. Third, in the quarter after dividend payment, the share price declines by 4%. Fourth, the change in dividends affects the share price volatility, so that if the dividend goes up by 1%, the share price will rise by 14.35%. Hence, there is a significant positive link between dividends and share prices.
Keywords: G32; G35; C12; C23; 330; corporate finance; dividend policy; dividend payment procedure; company value; share price volatility